An efficient negative acknowledgement–based transport protocol in 802.11 media streaming. (26th August 2014) - Suherman, Suherman; Al–Akaidi, Marwan
This paper considers the use of negative acknowledgement (NACK)–based transport layer protocols in video transmission over 802.11 networks. A study of various transport layer protocols that utilise NACK to acknowledge packet loss is presented. A new NACK packet scheduling is introduced to enhance the retransmission performance. A mathematical model and analysis are presented to compare protocol performances in relation to delay and packet loss. The analysis is then confirmed through simulations using the NS–2 simulator. Furthermore, this paper presents the outcomes of an experiment to verify the analysis and simulation results. The results show that reducing the number of NACK packets within one video frame could reduce effective loss rate and delay.